GOVERNMENT POLICY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Government policy define as an argues that the role of institutions needs to be recognized in resilience building because, while the technical aspects of mitigation measures are important, their acceptance by the institutions should not be underestimated. In Uganda for example operating outside the disaster management policy and established institutions during disaster relief may be disastrous to a particular organization or individual Ekotu, (2012). Fatemeh, (2011) argues for a synergy whereby civic engagement should serve to strengthen state institutions and where effective state institutions create an environment in which civic engagement is more likely to thrive. Government policy  has the following attributes, Efficiency, Impact, Effectiveness and Relevance (Brooks, 2011).